Demographic Characteristics of Mothers Who Delivered Children with Birth Defetcs: Demografi Ibu yang Melahirkan Janin dengan Kelainan - Yudianto B Saroyo; Christian Wijaya; Putri M T Marsubin (Indonesian Journal of Obstetrics and Gynecology, 2018)
Abstract Objective: to determine the characteristics and background of mothers who delivered neonates with birth defects. Methods: A retrospective study was used by evaluating the medical records of patients with birth defects in Dr. Cipto Mangunkusumo Hospital during the period between September 2014 and June 2016. Results: A total of 67 (1.85%) out of 3,619 infants who were born in Dr. Cipto Mangunkusumo Hospital during the period between September 2014 and June 2016 had birth defects. Forty-seven (70.1%) mothers of the subjects irregularly attend antenatal care. The most frequent maternal comorbid disease in this study was asthma, which was found in 4 (5.97%) mothers of the subjects. 48 (58.7%) subjects had birth weight under 2500 g. Conclusion: In this retrospective study, the main highlight is that 70.1% of the mothers who delivered neonates with birth defects did not attend antenatal care regularly. 58.7% of the neonates with birth defects had low birth weight. This study could be used as base for further research investigating about the role of antenatal care in early detection and/or the planning of delivery for babies with birth defects. Trends in babies with birth defects suggested that fetuses diagnosed with IUGR/SGA should be given special attention, as they were at increased risk for birth defects. Keywords: birth defect, maternal description Abstrak Tujuan: untuk mengetahui deskripsi/ciri-ciri dan latar belakang ibu yang melahirkan janin dengan kelainan bawaan. Metode: Studi retrospektif digunakan dengan menggunakan data sekunder rekam medis pasien dengan kelainan bawaan di Rumah Sakit Umum Pusat Nasional Dr. Cipto Mangunkusumo pada periode September 2014-Juni 2016. Hasil: Sejumlah 67 (1.85%) dari 3,619 neonatus didapatkan dengan kelainan bawaan di RSUPN Cipto Mangunkusumo pada periode September 2014-Juni 2016 . Sejumlah 47 (70.1%) ibu dari subjek tidak teratur dalam melakukan kunjungan antenatal care. Penyakit komorbid ibu yang paling banyak ditemukan dalam studi ini adalah asma, yang ditemukan dalam 4 (5.97%) subjek. 48 (58.7%) subyek memiliki berat lahir di bawah 2500 g. Kesimpulan: Pada studi retrospektif ini didapatkan 70.1% ibu yang melahirkan bayi dengan kelainan bawaan tidak melakukan kunjungan antenatal care. Didapatkan bahwa 58,7% bayi yang lahir dengan kelainan bawaan memiliki berat badan lahir rendah (BBLR). Studi ini dapat dijadikan sebagai landasan dilakukannya studi yang lebih besar untuk mengevaluasi peran antenatal care terhadap deteksi dini dan/atau perencanaan persalinan bayi dengan kelainan bawaan. Tren pada bayi dengan kelainan bawaan menunjukkan bahwa janin yang pada antenatal care didapatkan IUGR/SGA patut diperhatikan lebih untuk kecurigaan kemungkinan adanya kelainan bawaan. Kata kunci: deskripsi ibu, kelainan bawaan,